"Subnutrition effects during pregnancy and lactation on mitosis, apoptosis and androgen receptor expression in the rat testis". Issue 3 (31st December 2018) - Genovese, Patricia; Herrera, Emiliano; Riaño, Victoria; Bielli, Alejandro
Contents: In order to study the effect of undernutrition during gestation on the testicular development in rats and its impact on mitosis, apoptosis and the relative abundance of androgen receptor expression, twenty primiparous 3‐month‐old Sprague–Dawley ( Rattus norvegicus ) rats, weighing 246 ± 4.0 grams when the experiment began, were mated by the same male. Control group (CG), n = 10, fed ad libitum with water and rat chow and restricted group (RG, n = 10) fed throughout pregnancy and until birth with 40% of the ad libitum maternal daily feed intake. Litters from both groups suckled for 25 days, RG with 14 pups/litter and CG with 8 pups/litter. After weaning, all animals had access to ad libitum food and water. Testicular samples were taken from male pups at 2, 25 and 100 days of age. Immunohistochemistry was used to evidence androgen receptor (AR) expression in apoptotic (caspase 3‐positive) and proliferating (PCNA‐positive) cells. Three hundred nuclei of sustentacular (or Sertoli: SC), interstitial (or Leydig: LC), myoid (MC) cells as well as gonocytes (GC) were evaluated. Neither LC nor GC showed any differences between groups. However, SC androgen receptor (AR) positivity index in neonatal animals was lower in RG (1.27 ± 0.22 vs. 1.65 ± 0.17**). MC showed lower AR positivity index at 2 (2.69 ± 0.046 vs. 2.8 ± 0.055**) and 25 (1.34 ± 0.097 vs. 1.56 ± 0.1***) days of life; at 100 days of life, there was a greater number of apoptotic MC in the RG (8.5 ± 0.4 vs. 2.95 ± 1.1***). Thus, the present experiment demonstrates that the population dynamics of MC are affected by foetal programming due to undernutrition.